Aproveitamento das frações hemicelulósica do resíduo do processamento do girassol para produção de bioetanol - Camargo, Danielle (2012)
The researches on second generation ethanol, produced by agroindustrial wastes, have demanded special attention as a possible solution that can contribute to energy sustainability. Such production is based on lignocellulosic fiber conversion (cellulose and hemicellulose), which generates fermentable sugars that are biotransformed in bioethanol after some specific pretreatment and hydrolysis. The industries of extracting oil from sunflower seeds have also generated lignocellulosic residues known as sunflower cake and bran. They can be sources for recycling and profitable alternatives on converting biotechnological products with some trading interest. Thus, this trial aimed at evaluating ethanol production from cellulose and hemicellulose fractions of cake and bran, from the processing of sunflower seeds (Hellianhus annuus). After the description concerning contents of cellulose, hemicellulose and lignin, the residues were submitted to a mild acid hydrolysis with sulfuric acid, whose concentration of H2SO4 varied in 1, 2, 4 and 6% v/v, while times of hydrolysis in autoclave were (20, 40 and 60 minutes). After choosing the best of sunflower residue and treatment to obtain a hemicellulosic hydrolysate with high content of xylose and low content of inhibiting compounds, the detoxified hydrolyzate was fermented by the yeast Pichia stipitis ATCC 58376 at 30 °C with some stirring variations (100, 150 and 200 rpm). In order to obtain ethanol from cellulosic fraction, the remaining solid biomass from acid hydrolysis treatment was delignified at 1% NaOH and submitted to simultaneous saccharification and fermentation process (SSF) by yeast Kluyveromyces marxianus ATCC 36907, at 38 °C and 150 rpm. The enzymes concentrations varied at 10, 15 and 20 FPU/g of Cellulase complex NS22086 and 1/3, 1.5/3 and 2/3 of β-glucosidase in relation to NS22118 cellulase, both ones from "Novozymes Cellulosic Ethanol Enzyme Kit ". Regarding chemical composition, the cake has shown the following answers: 27.5, 33.16 and 32.18% of cellulose, hemicellulose and lignin, respectively, while for bran, the answers were: 32.93, 30.90 and 26.62% cellulose, hemicellulose and lignin, respectively. Treatment of sunflower bran with 6% H2SO4 and 20 minutes of hydrolysis resulted in a hemicellulosic hydrolysate with high concentrations of sugars (24.88 g/L xylose, 22.33 g/L glucose, 8.9 g/L arabinose and lower amounts of toxic compounds (1.59 g/L phenol, 1.93 g/L acetic acid, 0.0182 g/L furfural and 0.0514 g/L hydroxymethylfurfural). The stirring influenced the process of ethanol production by P. stipitis in hemicellulosic hydrolyzate, whose best results (ethanol 8.8 g/L, yield 0.23 g/g and productivity 0.12 g/Lh) were with 200 rpm stirring. In relation to the SSF process, the best conditions for ethanol production were 20 FPU/g cellulase and 15 CBU β-glucosidase. This resulted in 27.88 g/L ethanol, 0.35 g/g yield and 0.38 g/Lh productivity. In the same condition, the best efficiency of enzymatic conversion (EEC) was 21.95%. These are promising results since sunflower bran is available to produce second generation ethanol from both xylose and cellulose